The significance of conflicting discourses in a professional degree: assessment in undergraduate fine art practice. Issue 2 (4th March 2017) - Belluigi, Dina Zoe
Abstract : This paper expands on empirical research which revealed that, whether or not an institution's interpretative community was explicitly informed by outcomes-based assessment, the more powerful and implicit discourses that emerged in assessment practices were those of their professional practice and academic traditions. Tensions, between the emerging dominant discourses, had their roots in academic perspectives and traditions; professional practice(s) and ways of being; and the more recent educational development discourses. The significance of these tensions for the discursive positioning of staff and students is discussed, with suggestions made for possible ways to negotiate these problematics more purposefully